2020
DOI: 10.1002/fsn3.1877
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the volatile components of squid (illex argentinus) for different cooking methods via headspace–gas chromatography–ion mobility spectrometry

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 69 publications
0
15
1
1
Order By: Relevance
“…The aldehydes detected included pentanal, 3-methylbutanal, 2-methylbutanal, and hexanal; the alcohols detected included 1-butanol and 3-methyl-3-buten-1-ol; the ketones detected included acetoin, propyl methyl ketone, and 2,3-pentanedione; the esters detected included propyl acetate and ethyl 2-methylpropanoate; and the acid detected included acetic acid and propionic acid. Cui et al [ 23 ] analyzed the volatile components of squid ( Illex argentinus ) cooked with different cooking methods, detected 99 volatile compounds, and determined 43 specific volatile compounds. The difference of the results may be related to different detection and analysis methods, different squid varieties, processing temperature, and GC × IMS Library Search retrieval database.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aldehydes detected included pentanal, 3-methylbutanal, 2-methylbutanal, and hexanal; the alcohols detected included 1-butanol and 3-methyl-3-buten-1-ol; the ketones detected included acetoin, propyl methyl ketone, and 2,3-pentanedione; the esters detected included propyl acetate and ethyl 2-methylpropanoate; and the acid detected included acetic acid and propionic acid. Cui et al [ 23 ] analyzed the volatile components of squid ( Illex argentinus ) cooked with different cooking methods, detected 99 volatile compounds, and determined 43 specific volatile compounds. The difference of the results may be related to different detection and analysis methods, different squid varieties, processing temperature, and GC × IMS Library Search retrieval database.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease or increase in the concentrations of compounds in SMM might be attributable to the reaction or decomposition induced by thermal treatment. Cui et al [ 23 ] found the highest contents of 1-propene-3-methylthio, furaneol, linalool, and nonanoic acid in raw squid ( Illex argentinus ); heptanal and N, N-diethylethanamine in BO squid; furfural and 2-methyl-1-propanol in ST squid; and n-propyl acetate and acetic acid ethyl ester in SV squid, which are inconsistent with our results, and the possible reason is the difference of squid species. Deng et al [ 52 ] found the highest contents of acetoin, pentadecanoic acid, dimethylamine, furfural, and n-hexadecanoic acid in raw North Pacific squid ( Todarodes pacificus ); benzothiazole, n-hexadecanoic acid, benzaldehyde, benzyl alcohol, and pyridine in freeze-dried squids; acetoin, methional, pyrazine, 2,6-dimethyl, benzyl alcohol, and benzaldehyde in hot-air-dried squids; and acetoin, n-hexadecanoic acid, tetradecane, tetradecanoic acid, and benzothiazole in heat pump-dried squids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different lowercase letters in the same row mark significant differences (p < 0.05). Journal of Food Quality trimer), influenced by the content and attributes of the specific volatile substance [11,30,33]. Figure 2(a) (left to right) shows the volatile compounds of meatball were BF, DFF, and HAF, respectively.…”
Section: Volatile Flavor Compounds Of Meatballs Based On Hs-gc-imsmentioning
confidence: 99%
“…Figure 4 also shows that the kinds and contents of volatile components in HAF samples are more abundant than those in DFF samples, implying better flavor attributes. e volatile flavor components during meatball frying are very complicated, generally containing aldehydes, alcohols, ketones, terpene derivatives, hydrocarbons, and a small amount of organic compounds such as furan, thioether, and naphthalene [17,33]. In order to better characterize the changes of various volatile compounds, the relative content changes of volatile components in giant salamander meatballs with different frying methods were obtained according to the signal intensity of the compounds on the fingerprint, shown in Figure 5.…”
Section: Journal Of Food Qualitymentioning
confidence: 99%